Flux-cutting and flux-transport effects in type-II superconductor slabs in a parallel rotating magnetic field - Cortés-Maldonado, R.; Espinosa-Rosales, J.E.; Carballo-Sánchez, A.F.; Pérez-Rodríguez, F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The magnetic response of irreversible type-II superconductor slabs subjected to in-plane rotating magnetic field is investigated by applying the circular, elliptic, extended-elliptic, and rectangular flux-line-cutting criticalstate models. Specifically, the models have been applied to explain experiments on a PbBi rotating disk in a fixed magnetic field Ha, parallel to the flat surfaces. Here, we have exploited the equivalency of the experimental situation with that of a fixed disk under the action of a parallel magnetic field, rotating in the opposite sense. The effect of both the magnitude Ha of the applied magnetic field and its angle of rotation αs upon the magnetization of the superconductor sample is analyzed. When Ha is smaller than the penetration field HP, the magnetization components, parallel and perpendicular to Ha, oscillate with increasing the rotation angle. On the other hand, if the magnitude of the applied field, Ha, is larger than HP, both magnetization components become constant functions of αs at large rotation angles. The evolution of the magnetic induction profiles inside the superconductor is also studied.